Photogrammetry of an excavated ichnofossil by giant sloths (Megaichnus major) - Audi, Caroline [UNESP]; Meyer, Douglas; Yeuw, Tan Tjui [UNESP]; Baraldo, Kleber Barrionuevo [UNESP]; Fey, Jesica Daniela [UNESP]; Spanghero, Natalie Fernandes [UNESP]; Munhoz, Marcelo Schereiber [UNESP]; De Oliveira, Bruno Júlio [UNESP]; Buchmann, Francisco Sekiguchi [UNESP] (Sociedade Brasileira de Paleontologia, 2022)
During the Pliocene and Pleistocene, the extinct giant mammals that lived in South America had the burrowing behavior that, in the search for shelter and refuge, produced large ichnofossils called Megaichnus (paleoburrows). Megaichnus are biogenic structures in the form of tunnels and halls excavated by Folivora (Megaichnus major) and Cingulata (Megaichnus minor). On the ceiling and walls of these paleoburrows, it is possible to observe traces of excavation of these animals. Photogrammetry was performed by imaging M. major to generate the Three-Dimensional Digital Model (3DM). The paleoburrow is located in the Municipality of Doutor Pedrinho (Santa Catarina State) and was excavated in the sandstone of the Taciba Formation (Permian). The photographs were processed to generate the 3DM and the virtual reality interface with 3D glasses. The 3DMs are available for viewing on the Sketchfab website through the links (GoPro 4; https://skfb.ly/6RYyn) and (Nikon D60; https://skfb.ly/ooprJ). 3DM allows easy access to the ichnofossils, making it possible to study them remotely from anywhere in the world. The construction of 3DMs of the paleoburrows, through high-resolution photogrammetry, is an innovative proposal, and allows wide dissemination of knowledge about these structures.
FOTOGRAMETRIA DE UM ICNOFÓSSIL ESCAVADO POR PREGUIÇAS-GIGANTES (MEGAICHNUS MAJOR)
Keywords: 3D imaging; megafauna; paleoburrows; Quaternary